1987
DOI: 10.1172/jci112876
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of defective C3-receptor-mediated clearance by the reticuloendothelial system in patients with acquired immunodeficiency syndrome.

Abstract: The function of macrophage C3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1988
1988
2000
2000

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…In contrast, in vitro infection of monocyte-derived M with HIV-1 caused downregulation of CD11b (34,43). In addition, it was demonstrated that in vivo there is impaired CR3-mediated clearance of 51 Cr-labeled iC3b-coated autologous erythrocytes (44). These investigators also found normal levels of CD11b on HIVϩ patient monocytes, and, therefore, suggested that there is an impairment of M phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in vitro infection of monocyte-derived M with HIV-1 caused downregulation of CD11b (34,43). In addition, it was demonstrated that in vivo there is impaired CR3-mediated clearance of 51 Cr-labeled iC3b-coated autologous erythrocytes (44). These investigators also found normal levels of CD11b on HIVϩ patient monocytes, and, therefore, suggested that there is an impairment of M phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…These data too hint at previous exposure of phagocytes to IFN-7 challenge in vivo. Several other phenotypic and functional features of I FN-y-lreated phagocytes, such as low surface CD4 antigen levels [21], decreased C3-reccptor function [22], increased spontaneous and antibody-dependent cytotoxicity [20], have been observed in untreated phagocytes from HIV patients [23][24][25][26]. further suggesting a priming effect of circulating IFN-}' on these cells.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that a reduced immunologic response due to the immune deficit in HIV-1-infected patients tor [23], that would give rise to decreases in phagocytosis [24,25]; in myeloperoxidase activity [26] with associated decreases spares the brain from the inflammatory alterations that are produced in the initial phases of meningitis and are directly in bacterial lytic activity; and in antibody-mediated cytotoxic activity have been described among HIV-1-infected patients related to mortality. [27].…”
Section: Patients Infected With Hiv-1 Have a Primary Defect In Cellu-mentioning
confidence: 99%